Ответы и объяснения

  • AlbuRin
  • светило науки
2013-06-26T03:13:09+00:00

log_3 (3x^2) * log_3 x  =  1

ОДЗ         х >0

log_3(3x^2)  +  log_3 x   -   1   =   0

Заменим    log_3 3x  =  z,     log_3 (3x^2)   =  x^2   Ролучим

z^2  +  z   -  1   =  0

D  =  V(b^2  -  -4ac)  =  V(1^2   -4*(-1))  =  V5

x     =    -b  +  VD  =   -1  +  V5  >0  удовлетворяет     ОДЗ

  1

 

x     =   -d  -  VD  =  -1  -  V5<0      не   удовлетворяет      ОДЗ

  2

 

Ответ.         -1    +   V5

2013-06-26T05:52:25+00:00

log_3 (3x^2) * log_3 x  =  1

ОДЗ         х >0

log_3(3x^2)  +  log_3 x   -   1   =   0

Заменим    log_3 3x  =  z,     log_3 (3x^2)   =  x^2   Ролучим

z^2  +  z   -  1   =  0

D  =  V(b^2  -  -4ac)  =  V(1^2   -4*(-1))  =  V5

x     =    -b  +  VD  =   -1  +  V5  >0  удовлетворяет     ОДЗ

  1

 

x     =   -d  -  VD  =  -1  -  V5<0      не   удовлетворяет      ОДЗ

  2

 

Ответ.         -1    +   V5